KONSEP HARMONI ANTARA MANUSIA, ALAM, DAN TUHAN SEBAGAI SEBUAH KEARIFAN LOKAL DALAM MENGHADAPI BENCANA BAGI MASYARAKAT JAWA - Hastinia Apriasari (Republic of Indonesia Defense University, 2021)
Indonesia is a country that is prone to disasters, both natural and non-natural. Various efforts were made to minimize the impact of disasters with mitigation efforts. Disaster mitigation efforts will be easier to do if the social capital of a community can be recognized properly. Java as part of Indonesia is famous for its philosophy of life which is the basis for patterns of attitude and behavior. This philosophy can become social capital in disaster mitigation efforts. This paper will discuss how the harmonization of humans, nature, and God as a local wisdom that influences disaster mitigation efforts for the Javanese community with the literature review method. The findings of the study are that the Javanese people have a philosophy of life that has existed for hundreds of years. In the aspect of spirituality and religiosity contained in the concept of sangkan paraning dumadi can have a positive influence in dealing with disasters. Self-harmonization with nature in hamemayu hayuningbawana and hamemasuh malaning earth is a way to re-balance relations with the environment and nature if damage has occurred. In addition, social relations of helping or sambat sinambat can create social revival after a disaster occurs.